Designing persuasive application to encourage physical activity at workplace among older workers - Mohd Mohadis, Hazwani; Mohamad Ali, Nazlena (Institute of Electrical and Electronics Engineers Inc., 2016)
Regular physical activity are vital for prevention and treatment of chronic diseases, which are highly prevalent among older workers aged 50 years old and above. However, maintaining active lifestyle was challenging for older workers due to prolong hours of sedentary behaviour at workplace. In this study, we attempt to identify design requirements of a persuasive smartphone application aiming to encourage physical activity at workplace among older workers. We applied a triangulation of user-centred design techniques that includes think-aloud, parallel prototyping and participatory design methods aiming to identify any usability problems, functionality issues, privacy concern, information sharing and visualization. Our older workers indicate that contextual awareness, visibility of cause-and-effect relationship, accuracy of collected data, information sharing and privacy control are highly imperative to be integrated into the design of smartphone-based intervention targeting at enhancing their physical activity behaviour in workplace environment.